Prevalence of Eimeria spp. with associated risk factors in dairy calves in Sylhet, Bangladesh - Liton Chandra Deb; Syed Sayeem Uddin Ahmed; Chandan Chandra Baidhya; Nirmalendu Deb Nath; Sumon Ghosh; Suman Paul (Veterinary Medicine and Science, 2022)
Abstract Background Bovine eimeriosis is thought to be very important for the productivity and health of cattle all over the world. Despite the importance of cattle farming in Sylhet, little is known about the prevalence of bovine Eimeria spp. and the risk factors connected with it. Objectives We conducted a study to evaluate the prevalence, species diversity and associated risk factors of Eimeria spp. in a population of 50 cattle farms from 12 upazilas (sub‐district) in Sylhet district. Methods Faecal samples were collected randomly from a total of 554 calves ranging in age from 1 month to 2 years old during a period of 7 months. We used Flotation and McMaster techniques for parasitological examination. Species identification was done by using their morphological and morphometric characteristics. Results Out of 554 calves, 308 were found to be positive for Eimeria species (55.60%). Seven species of Eimeria were identified. Among the identified species, E. bovis (38.98%), E. zuernii (26.17%) and E. alabamensis (22.38%) were found to be the most prevalent species. Mixed and species‐specific Eimeria infection were (24.73%; 95% CI 21.32–28.49) and (30.87%; 95% CI 27.17–34.84), respectively. In addition, the highest prevalence was observed at Zakigonj (68%; 95% CI 58.34–76.33) and the lowest at Companygonj (40%; 95% CI 30.94–49.80). Eimeria species intensity ranged between 50 and 76,550 oocyst per gram of faeces. Analysis of associated risk factors by using multivariate logistic regression analysis revealed that age, gender and body condition were significantly (p < 0.05) associated with Eimeria infection. Conclusions Based on these present findings, it can be assumed that ‘coccidia belong to the most prevalent pathogens in the population of calves in the study area’. Thus, the findings of this study could be used as tools for adoptive surveillance and effective control and prevention of the disease in cattle populations in this region.